"Usandheden må leves" - Genoptagelsen af Kierkegaard i eksistentialismen - Hackel, Manuela (Slagmark - Tidsskrift for idéhistorie, 2018)
Kierkegaard is the ‘father’ of existentialism. This claim, however, seems to be a contradiction in terms. The first part of the paper offers a fundamental reflection on the question of whether a subjective thinking like Kierkegaard’s can survive his death and in what form. In its second part, the paper inquires into the concrete reception of Kierkegaard’s thinking in the atheistic branch of existentialism (Sartre, Beauvoir, Camus). The paper will examine how Kierkegaard’s fundamental themes and concepts such as understanding, freedom/choice, des-pair, and anxiety are appropriated and transformed on the basis of a changed historical and philosophical situation. It will be argued that it is only in this way that the reception of Kierkegaard will avoid being a hollow repetition and be a lively conversation.